PENGARUH KREDIBILITAS DAN TRUSTWORTHINESS BEAUTY INFLUENCER DI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH - anastasia cresentia; Romauli Nainggolan (Universitas Ciputra Surabaya, 2021)
In this era, social media influencers play an important role in marketing by introducing products to the followers. Then, there are a lot of cosmetic companies that take a look at theopportunity and use influencer service to promote the products. This research analyzes the effect of beauty influencers’ credibility and trustworthiness on purchase decision of Wardah cosmetic products. The population in this research is women who are 20 to 35 years old that use Instagram, follow beauty influencers, and use Wardah products. Sampling determination that is used in this research is purposive sampling with the total sample of 100.This research uses quantitative method with Multiple Linear Regression analysis. The results of this research indicate that credibility and trustworthiness variables affect positive on purchase decision. The implication of this research can help the researcher and marketer to maximize promotion through beauty influencers and consumers’ purchase decision among targeted respondents, give strategy and effective strategy investment practice for cosmetic industry management and offer practical guidance for communication expert, brand and marketing manager that have the purpose to develop the relationship with beauty influencer in beauty industry by creating brand equity and sustainable bond with online customers.Keywords: credibility, trustworthiness, purchase decision, beauty influencer, Instagram